Clinical and Epidemiological Profile of Herpes Zoster; A Cross-Sectional Study from Tertiary Hospital - Paudel, Vikash; Pandey, Buddhi Raj; Tripathee, Richa; Tripathee, Rishabh Dev; Sitaula, Shreema; Dhakal, Prabin; Shrestha, Dwarika Prasad (Med Phoenix, 2018)
Background: Herpes zoster is dermatomal neuropathic disease caused by reactivation of varicella zoster virus, characterized by vesicobullous eruptions. Although, being a common cause of morbidity, there are few clinicepidemiological studies and the studies regarding the knowledge and practice among the patients are nominal. Methods: This was descriptive observational study which included 100 consecutive patients with herpes zoster who presented to Department of Dermatology and Venereology in a Teaching Hospital, Kathmandu during the period from July 2014 to June 2015. Results: The annual incidence was 0.55%. Seventy two percent were males and 28 percent were females with the M: F=2.5:1. The average age of patients and mean duration of disease was 40.4 years and 5.5 days respectively. Ninety five percent were managed at OPD and 5 % of them needed hospitalization. Most common dermatome involved was thoracic (50%) followed by cervical (20%). Twelve percent had one or more provocative features including diabetes, steroid use, chemotherapy, surgical trauma etc. Twenty patients had definite history chicken pox. Twenty-five percent had local complication at the time of presentation. Fifty two percent had themselves identified the lesion as herpes zoster. However, only 10 had some knowledge about it. Twelve percent had visited traditional healers prior to hospital arrival. Conclusions: The results show varied clinicoepidemiologic patterns of herpes zoster. Major patient have less knowledge about it. A larger study would be necessary for better clinical, epidemiological and social behavioral data. Because of ignorance and tradition, awareness program should be conducted to reduce potential complications. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 60-65